Respuesta :
Answer: 11\sqrt{2} - 5\sqrt{7}
Option (A) is the correct answer.
Step-by-step explanation:
9\sqrt{2} - 3\sqrt{7} + \sqrt{8} - \sqrt{28}
Now, \sqrt{8} = \sqrt{2 \times 2 \times 2} = 2\sqrt{2}
\sqrt{28} = \sqrt{2 \times 2 \times 7} = 2\sqrt{7}
∴ 9\sqrt{2} - 3\sqrt{7} + \sqrt{8} - \sqrt{28}
= 9\sqrt{2} - 3\sqrt{7} + 2\sqrt{2} - 2\sqrt{7}
= 9\sqrt{2} + 2\sqrt{2} - 3\sqrt{7} - 2\sqrt{7}
= 11\sqrt{2} - 5\sqrt{7}
Therefore option (a) is the correct answer.
Step-by-step explanation:
Answer:
A) [tex]11\sqrt{2} - 5\sqrt{7}[/tex]
Step-by-step explanation:
[tex]9\sqrt{2}[/tex] and [tex]3\sqrt{7}[/tex] are already in simplest form. However, [tex]\sqrt{8}[/tex] can be further simplified to [tex]2\sqrt{2}[/tex], and [tex]\sqrt{28}[/tex] can also be further simplified to [tex]2\sqrt{7}[/tex]. Combining like terms (terms with the same radical) gives us a final answer of [tex]11\sqrt{2} - 5\sqrt{7}[/tex].
Hope this helped! :)